2012
DOI: 10.3998/ark.5550190.0013.513
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new enantiopure dimethyl-substituted pyridino-18-crown-6 ethers containing a hydroxymethyl, a formyl, or a carboxyl group at position 4 of the pyridine ring for enantiomeric recognition studies

Abstract: An enantiomerically pure dimethyl-substituted pyridino-18-crown-6 ether containing a hydroxymethyl group at position 4 of the pyridine ring [(S,S)-1] has been prepared. This by Swern oxidation gave the formyl-substituted [(S,S)-2], then by further oxidation carboxy-substituted [(S,S)-3] pyridino-18-crown-6 ether derivatives. These enantiopure dimethyl-substituted pyridino-18-crown-6 ethers [(S,S)-1─(S,S)-3] are good candidates for enantiomeric recognition studies and also very useful precursors for enantiosele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We obtained the desired PRDs in two to five steps (Scheme ). We performed a Fenton’s oxidation-type reaction (I, Scheme ) by treating the commercially available dimethyl 2,6-pyridinedicarboxylate ( 1 ) with H 2 O 2 in a solution of Fe­(ClO 4 ) 2 in methanol and water in the presence of HClO 4 to introduce the hydroxymethyl group in position 4 of the pyridine core . Hence, we protected the hydroxy group of the intermediate 2 as a tetrahydropyranyl (THP) ether to perform the subsequent transesterification and amidation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the desired PRDs in two to five steps (Scheme ). We performed a Fenton’s oxidation-type reaction (I, Scheme ) by treating the commercially available dimethyl 2,6-pyridinedicarboxylate ( 1 ) with H 2 O 2 in a solution of Fe­(ClO 4 ) 2 in methanol and water in the presence of HClO 4 to introduce the hydroxymethyl group in position 4 of the pyridine core . Hence, we protected the hydroxy group of the intermediate 2 as a tetrahydropyranyl (THP) ether to perform the subsequent transesterification and amidation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale, multiwell interwell tracing also necessitates the deployment of multiple chemically distinct tracer entities, particularly so in the case of simultaneous tracer injection. Previous experiments have shown that chemical modification of a ligand such as DPA may be achieved via functionalization at the pyridyl 4-position to generate various derivatives, the exact nature of which are application-dependent. For our purposes, we propose that simultaneous full-field deployment of chemical water (nonpartitioning) tracers may be realized in modular synthetic sequences that enable access to higher-order molecular constructs based on a parent tracer compound through chemical conjugation of differing molecular fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The macrocyclization reaction was carried out with pyridino-2,6-dicarbonyl dichlorides (14)(15)(16) [prepared in situ from the corresponding dicarboxylic acids (17 23,24 , 18 25,26 and 19 [25][26][27][28] )] and chiral diamines [(S,S)-9, (S,S)-10] and resulted in new amide type pyridino-crown ethers [(S,S)-1-(S,S)-6, see Scheme 2]. These reactions used the high dilution technique.…”
Section: Scheme 1 Preparation Of New Methyl-[(ss)-9] and Isobutyl-smentioning
confidence: 99%